Nişanın sona ermesinin hukuki sonuçları - Şahin, Ertuğrul (My University, 2016)
Türk Medeni Kanunu nişanlanmayı aile hukuku içerisinde düzenleyerek hukuki bir statüye kavuşturmuş, yalnızca örf ve adet gereği değer atfedilen bir kurum olmaktan çıkarmıştır.Türk Medeni Kanunu'nun 120-122. maddelerinde nişanın sona ermesinin hukuki sonuçları düzenlenmiştir. Söz konusu maddelere göre, nişanın sona ermesi halinde maddi tazminat, manevi tazminat ve hediyelerin geri verilmesi talepleri ileri sürülebilecektir.Bu çalışmada nişanın sona ermesinin hukuki sonuçları, “maddi tazminat”, “manevi tazminat” ve “hediyelerin geri verilmesi” ana başlıkları altında doktrin ve yargı kararları ışığında incelenecektir. Bu konuda yeni tarihli eserlerde bile çok eski yargıtay kararlarına atıf yapıldığı, atıf yapılan kararlarında genellikle küçük bir kısmının yahut yanlızca tarih ve sayısının dipnotta belirtildiği görülerek yargıtay kararlarına ulaşma sıkıntısı bulunduğu değerlendirilmiştir. Yargıtay tetkik hakimi olarak görev yapmanın sağladığı yargıtay kararlarına erişebilme imkanından ötürü çok sayıda güncel yargıtay kararı en can alıcı kısımlarıyla eklenerek çalışma zenginleştirilmiş, bu sayede hem yargıtayın konuyla ilgili güncel görüşleri açıklanmış hem de bundan sonra yapılacak çalışmalar için kaynak oluşturulmuştur. Maddi tazminat, Manevi Tazminat, Hediyelerin İadesi.

Turkish Civil Code regulated engagement within the family law and helped it gain a legal status, making it more than an institution that is valued merely on customary basis. Legal consequences of termination of an engagement is regulated in Articles 120 to 122 of Turkish Civil Code. According to the mentioned articles, material damages, non-pecuniary damages and return of gifts can be claimed in case of termination of engagement.In this study, legal consequences of termination of an engagement will be analyzed in the light of doctrines and judicial decisions, under the main headings of “pecuniary damages”, “non-pecuniary damages” and “return of gifts”. It has been interpreted that there is a problem in accessing the Supreme Court decisions, upon seeing that very old Supreme Court decisions are referred to in this respect even in the new-dated works and that mostly a short part of the referred decisions or merely the dates and numbers of the same decisions are indicated in the footnote. Nevertheless, a large number of current Supreme Court decisions have been added completely and enriched the study, thanks to the opportunity of accessing supreme court decisions, provided by serving as an investigation judge at the Supreme Court, and, by this means, not only the current opinions of the supreme court regarding the subject have been explained, but also a resource has been created for the next studies to be carried out. Key Words: Engagament, Pecuniary Damages, Non-Pecuniary Damages, Return Of Gifts
Keywords: Aile hukuku; Hukuk ve mevzuat; Nişanın bozulması; Türkiye; Türrkiye